The species diversity and phylogeny of the genus Siphlonurus Eaton, 1868 from China (Ephemeroptera: Siphlonuridae) - Qiang, Xin He; Zhou, Chang Fa (Zootaxa, 2025)
The Siphlonurus Eaton, 1868 is a diverse genus but has never been systematically researched in China previously. In this review, nine species are recognized, including two new species (S. orientalis sp. nov. and S. polyspineus sp. nov.) and two new records for China (S. lacustris Eaton, 1870 and S. zhelochovtsevi Tshernova, 1952). Among the other five species, two (S. davidi (Navás, 1932) and S. dongxi Li et Tong, 2023) have the same wing coloration as S. orientalis sp. nov., while the other two (S. chankae Tshernova, 1952 and S. immanis Kluge, 1985) have clean wings similar to S. zhelochovtsevi. Another previously reported name, S. binotatus sensu Imanishi, 1940 (nec S. binotatus (Eaton, 1892)) is now regarded as the ninth species S. palaearcticus (Tshernova, 1930) in China. Morphologically, the nymphs of the new species S. orientalis sp. nov. can be distinguished by unfused oblique stripes on sterna, shapes of gills and maxillary palps, while males can be further identified by shapes of genitalia and legs as well as sternal color. The other new species S. polyspineus sp. nov. has notably spiny penis in adult stage and sparse and stout spine-like setae on tergum X in nymphal stage. Detailed photographs of nymphal and imaginal structures are provided, along with diagnostic tables and keys. Molecularly, the phylogenetic tree (based on mitochondrial protein-coding genes, constructed using Bayesian inference) reveals that S. palaearcticus occupies the basal position. The remaining species form two distinct geographic groups: (1) three southern species share similar wing coloration, male genitalia and nymphal abdominal spines and gills, and (2) five northern species exhibit transparent wings, alike abdominal markings in adults and similar nymphal wingpads and gills. In terms of genetic gaps of COI sequence, Chinese Siphlonurus show narrow intraspecific ranges (0.34–2.26%) but relatively high interspecific span (8.95–21.08%) except that the populations of S. lacustris have even 5.17% difference.